Military-Applied Means of Physical Education in Pre-University Educational Institutions of the Russian Ministry of Defence - D. V. Vinograd; A. V. Zykov (Образование и наука)
Introduction.. The main purpose of pre-university educational institutions of the Ministry of Defence ofRussia, e.g. Suvorov Military Schools, Nakhimov Naval Schools, presidential schools and cadet corps, is to educate graduates, who are highly motivated and sufficiently prepared for military vocational activities, including graduates’ general physical fitness. Successful performance of the task is complicated by the fact that educational process in such organisations has a general educational orientation, which is common for the entire system of school education. However, it is obvious that the specifics of the mission of preuniversity educational institutions of the Ministry of Defence of the Russian Federation requires more intensive physical activities, which improve health and increase physical endurance of students, taking into account their age-specific physiological characteristics. In this regard, it is necessary to develop a variable methodological block as a supplement to an invariant part of the main programme of physical culture, which will be aimed at stimulating the development of motor and power capabilities, skills and professionally significant qualities of future military personnel.The aim of the research was to select and scientifically justify the introduction of appropriate and effective means for high-school students’ physical education in pre-university educational institutions of the Ministry of Defence ofRussia.Methodology and research methods. To identify the appropriate ways of solution of the problems of profile physical education of potential officers at the stage pre-professional development, the methodological framework was based on the theory of physical culture and sport, individually-modular approach to the development of the system of professional and applied physical training, its principles and regularities, conceptual provisions of health preservation in adolescence and youth. In the course of the research, the authors thoroughly studied the scientific and methodological sources, regulatory and legal base of the organisation of educational process, questions of its planning and control of all forms and activities of students’ physical training in military schools. The following methods were applied: interview, pedagogical observation, questionnaire survey, technique of entrance and final testing of selection of the research participants, formative experi ment, monitoring, comparative analysis and systematisation of indicators (resultant scores) of sports achievements of examinees. Experimental data were processed by the methods of mathematical statistics.Results and scientific novelty. The selection of means of physical training in pre-university all-service military and naval educational institutions was made on the basis of theoretical and statistical material of analytical review and collected empirical data and pedagogical experience in 17 pre-university educational institutions of the Ministry of Defence of Russia (n = 607). The list of the most productive means is made. The quantitative ratio of military-applied methods, which positively influence the system of physical training in the 10th-11th grades, is established. The pilot testing showed that systematic use of special training exercises of military-applied orientation significantly improves the indicators of physical training of students. The analysis of students’ questionnaires before and after the experiment revealed strengthening of students’ moral stability, growing interest in military science and motivation to studying of an applied training material, as well as significant increase in the number of applicants seeking to continue their training in higher educational institutions of the Ministry of Defence of the Russian Federation and to dedicate their lives to military service. The proposals and practical recommendations on purposeful introduction of complexes of specialised physical exercises and elements of disciplines of military-applied sports to educational process are formulated.Practical significance. The results of the research can be employed to plan and organise physical training of high-school students of pre-university educational institutions of the Ministry of Defence ofRussia as additional programme and methodological support at the initial stage of military-applied physical training of future military specialists.